Intrauterine food restriction impairs the lipogenesis process in the mesenteric adipocytes from low-birth-weight rats into adulthood - Andreotti, Sandra; Komino, Ayumi Cristina Medeiros; de Fatima Silva, Flaviane; Ramos, Ana Paula Almeida; Gil, Noemi Lourenço; Azevedo, Gabriela Araujo; Sertié, Rogerio Antonio Laurato; Lima, Fabio Bessa; Landgraf, Richardt Gama; Landgraf, Maristella Almeida (Frontiers in Endocrinology, 2023)
Background: Intrauterine food restriction (IFR) during pregnancy is associated with low birth weight (LBW) and obesity in adulthood. It is known that white adipose tissue (WAT) plays critical metabolic and endocrine functions; however, this tissue's behavior before weight gain and obesity into adulthood is poorly studied. Thus, we evaluated the repercussions of IFR on the lipogenesis and lipolysis processes in the offspring and described the effects on WAT inflammatory cytokine production and secretion. Methods: We induced IFR by providing gestating rats with 50% of the necessary chow daily amount during all gestational periods. After birth, we monitored the offspring for 12 weeks. The capacity of isolated fat cells from mesenteric white adipose tissue (meWAT) to perform lipogenesis (14C-labeled glucose incorporation into lipids) and lipolysis (with or without isoproterenol) was assessed. The expression levels of genes linked to these processes were measured by real-time PCR. In parallel, Multiplex assays were conducted to analyze pro-inflammatory markers, such as IL-1, IL-6, and TNF-α, in the meWAT. Results: Twelve-week-old LBW rats presented elevated serum triacylglycerol (TAG) content and attenuated lipogenesis and lipolysis compared to control animals. Inflammatory cytokine levels were increased in the meWAT of LBW rats, evidenced by augmented secretion by adipocytes and upregulated gene and protein expression by the tissue. However, there were no significant alterations in the serum cytokines content from the LBW group. Additionally, liver weight, TAG content in the hepatocytes and serum glucocorticoid levels were increased in the LBW group. Conclusions: The results demonstrate that IFR throughout pregnancy yields LBW offspring characterized by inhibited lipogenesis and lipolysis and reduced meWAT lipid storage at 12 weeks. The increased serum TAG content may contribute to the augmented synthesis and secretion of pro-inflammatory markers detected in the LBW group.